How Do Feminist-Identified Women Cope With Discrimination? A Feminist Standpoint and Grounded Theory Study. (September 2018) - Watson, Laurel B.; Flores, Mirella J.; Grotewiel, Morgan; Brownfield, Jenna M.; Aslan, Sara; Farrell, Michelle
Women experience a higher incidence of mental health concerns compared to men, and scholars have located these challenges within a discriminatory sociocultural context. Although scholars have suggested that feminist attitudes may shield women from discrimination, research on the protective role of feminist attitudes is discrepant and suggests that there are distinct differences between those who do and do not self-identify as feminist; namely, self-identifiers may be more protected in the face of discrimination. Utilizing grounded theory and intersectional feminist standpoint methodologies, in this study we sought to understand the ways that self-identified womanist and feminist women cope with discrimination. We found that women's feminist and cultural identities intersected, each informing the other and influencing coping mechanisms and well-being. Moreover, results demonstrated that feminist women call upon a variety of different coping mechanisms in response to discrimination, including advocacy, social support, self-care, cognitive processes, disengagement, connecting to one's femininity, and religion and spirituality. Although possessing a feminist and/or womanist identity appeared to be protective in some cases, at other times it did not. Some participants expressed feeling marginalized from the feminist community and felt that their greater awareness of oppression was an additional source of distress. Based on these findings, we provide suggestions for mental health clinicians and research scholars.